Circulatory Insufficiency and Hypotension Related to the Ductus Arteriosus in Neonates - Rios, Danielle R.; Bhattacharya, Soume; Levy, Philip T.; McNamara, Patrick J. (Frontiers in Pediatrics, 2018)
The biological role of the ductus arteriosus (DA) in neonates varies from an innocent bystander role during normal postnatal transition, to a supportive role when there is compromise to either systemic or pulmonary blood flow, to a pathological state in the presence of hemodynamically significant systemic to pulmonary shunts, as occurs in low birth weight infants. Among a wide array of clinical manifestations arising due to the ductal entity, systemic circulatory insufficiency and hypotension are of significant concern as they are particularly challenging to manage. An understanding of the physiologic interplay between the ductus arteriosus and the circulatory system is key to developing appropriate targeted therapeutic strategies. In this review, we discuss the relationship of systemic hypotension to the DA, emphasizing the importance of critical thinking and a precise individual approach to intensive care support. We particularly focus on the variable states of hypotension arising directly due to a hemodynamically significant DA or seen in the period following successful surgical ligation. In addition, we explore the mechanistic contributions of the ductus to circulatory insufficiency that may manifest during the transitional period, states of maladapted transition (such as acute pulmonary hypertension of the newborn), and congenital heart disease (both ductal dependent and non-ductal dependent lesions). Understanding the dynamic modulator role of the ductus according to the ambient physiology enables a more precise approach to management. We review the pathophysiology, clinical manifestations, diagnosis, monitoring, and therapeutic intervention for the spectrum of DA-related circulatory compromise.